GENDER SPECIFICS OF THE COMBINATION ANTIHYPERTENSION THERAPY EFFICACY IN PATIENTS WITH ARTERIAL HYPERTENSION AND ISCHEMIC HEART DISEASE - V. V. Skibitsky; E. V. Gorodetskaya; A. V. Fendrikova; E. A. Kudryashov (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To evaluate gender specifics of the efficacy of combination antihypertensive therapy by zofenopril and valsartan by QD or BID schedule in patients with arterial (AH) and stable coronary heart disease (CHD).Material and methods. Totally 98 men and 100 women were included with AH and CHD, who were randomized into 6 groups according to their gender differences and type of the therapy taken: I and IV groups (women and men) – zofenopril 30 mg/day in the morning, II and V groups (women and men) – valsartan 160 mg in the morning, III and VI groups (men and women) – valsartan 80 BID. All patients took β-adrenoblocker metoprolol succinate and diuretic hydrochlorothiazide. Follow-up period was 24 weeks. At the baseline and in 24 weeks, also ambulatory blood pressure monitoring performed (ABPM).Results. In men zofenopril intake and valsartan BID led to the achievement of target blood pressure values in most of the patients, as significant increase of the main ABPM parameters and profile normalization in 70% and 66,7% patients, resp. In women there were more patients with target BP, more significant positive changes in ABPM with “dipper” profile in 78,8% cases in the group of BID valsartan.Conclusion. In AH and stable CHD maximum antihypertensive efficacy in men was shown with ACE inhibitor zofenopril and ARA valsartan BID, in women – in valsartan, especially two times per day.